ЧЕТ ТИЛИ ДАРСЛАРИДА ТАЛАБАЛАРНИНГ ИЖОДИЙ ҚОБИЛИЯТЛАРИНИ РИВОЖЛАНТИРИШ МУАММОСИНИНГ ДОЛЗАРБЛИГИ (инглиз адабиёти доирасида) - Ескараева, С.А. (SCIENCE and SOCIETY, 2022)
The article considers the importance of developing students’ creative thinking in foreign language classes. The classification of methods and techniques aimed at developing the creative activity of students, allowing them to think independently, is given.